Addition of small amounts of graphene oxide in the polyol during the synthesis of waterborne polyurethane urea adhesives for improving their adhesion properties. (January 2021) - Tounici, Abir; Martín-Martínez, José Miguel
Abstract: Mixtures of polyadipate of 1, 4-butanediol polyol and different small amounts (0.01–0.10 wt%) of graphene oxide (GO) were added during the synthesis of waterborne polyurethane urea dispersions (PUDs) carried out with the acetone method. The addition of 0.02–0.04 wt% GO increased the T-peel strength of plasticized poly (vinyl chloride)/PUD/plasticized poly (vinyl chloride) joints whereas the addition of 0.05–0.10 wt% GO increased the single lap-shear strength of stainless steel/PUD/stainless steel joints. The improved adhesion of the PUDs containing GO was ascribed to the creation of covalent interactions between the surface groups on the GO surface and the NCO groups of the isocyanate during prepolymer formation, creating new urethane groups; during the phase inversion, the covalently bonded GO sheets were embedded between the polyurethane urea chains inside the PUD particles, this changed the degree of phase separation between the hard and the soft segments. When more than 0.04 wt% GO was added, some GO particles cannot be covalently bonded to the prepolymer during the PUD synthesis but they agglomerated and physically "trapped" between the polyurethane urea chains. As a consequence, the adhesion properties of the PU + GO films were different in the PU films containing 0.01–0.04 wt% GO and the ones containing 0.05–0.10 wt% GO.